Mechanical Characterisation of Coconut Shell Concrete with Quarry Dust and Saw Dust as Fine Aggregate Using Coconut Fibre - S, Anandh; K, Gunasekaran (International Journal of Engineering and Technology, 2018)
This research investigates the mechanical properties of quarry dust and sawdust as fine aggregate in coconut shell concrete. The mechanical properties of concrete are increased by the addition of fibres and it is added in various percentages (1%, 2%, 3%, 4%, 5%). The tests was conducted with both controlled and coconut shell concrete and found optimized value of sawdust replacement to be 5%.Â For coconut shell concrete, fibres with aspect ratio 66.67 and for controlled concrete, fibres with aspect ratio 83.34 were used based on previous optimisation of fibre research.Â Compressive test results shows that coconut shell sawdust concrete with 2% of fibre yields maximum strength whereas in coconut shell quarry dust concrete maximum strength was attained with 4% of fibres. The results obtained were utilized for other experimental tests (split-tensile, flexural, impact and bond strength) which in turn compared with controlled concrete with fibres and coconut shell concrete with fibres.Â Â